From cell phones to conflict? Reflections on the emerging ICT–political conflict research agenda. (May 2015) - Dafoe, Allan; Lyall, Jason
From mobilizing masses to monitoring rebels, information and communication technologies (ICT) are transforming political conflict. We reflect on the contributions made by the articles of this special issue to the emerging ICT–political conflict research agenda, highlighting strengths of these articles, and offering suggestions for moving forward. Elaborate theory is crucial: it informs our standards of evidence, our choice of statistical models, our tests of competing theories, and our efforts to draw appropriate generalizations. Qualitative data is often neglected as a source of evidence, especially for evaluating the many competing mechanisms in this literature. Alternative explanations for results should be taken seriously, especially more mundane ones like confounding, measurement, and selection biases. We discuss in detail the risk that measurement bias could account for the prominent association between cellular coverage and (reported) conflict, and recommend several ways of evaluating and bounding this risk. We discuss the problem of temporal and spatial dependence for statistical inference – a problem that is often present for studies of ICTs – and point out that methodological solutions rely on (rarely stated) causal assumptions. Finally, we highlight key areas for future research, recommend a commitment to transparency best practices, and conclude with a discussion of the policy implications of this research.